Students’ English Proficiency: The Case of One Madrasah in Jambi City - HILMA SURYANI; SHYNTA AMALIA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2018)
This present study aimed to find out the senior high school students’ English proficiency. The study employed descriptive quantitative design. It took place at Madrasah Aliyah Labor Kota Jambi. There were 104 students of Madrasah Aliyah Labor purposefully selected in the study. The data were collected through English proficiency test for basic users namely Key English Test (KET). Descriptive statistics was employed to analyze the data. The result of this study revealed that four students (3.8%) were categorized as beginners (level A1) while the rest (96.2%) were not included in the entry level of Common European of Reference for Languages (CEFR) as their scores were lower than those of the beginner level. Moreover, based on the result of reading and writing test in KET analyzed by using the criteria used at school, the students scored low in both sessions.